Costs of F-18-FDG PET with a Satellite Concept: Update - Lottes, G.; Schober, O. (Nuklearmedizin - NuclearMedicine, 2000)
Aim: In an earlier study (study I) we had calculated the costs for FDG-PET investigations with our satellite concept (19). 433 patients were included in the study. Compared to the general indications for PET examinations the proportions of investigations were somewhat untypical: Both parameters have changed actually. Therefore we carried out a renewed data analysis (study II). Methods: All economic parameters were kept, in order to ensure the comparability of both studies. Only an adjustment of the costs to actual conditions was performed. Results: Proportions of investigations: Oncology 63%, Neurology 28%, Cardiology 9%; 3.5 investigations per working day. According to the increased number of investigations the structure of the total costs (DM 1601831) shows a small rise of the percentage costs for the FDG (41% to 42%) and a percentage decrease of the fixed overheads (48% to 43%). The percentage of personnel costs has increased (11% to 15%), the average cost per investigation has diminished: They amounted to DM 2783 in the earlier study (ranging from DM 2458 to 3463). The new data analy-sis results in the average cost of DM 2366 (-15%) per investigation (ranging from DM 2114 to 2840). Exemplary calculations show that a minimum of the costs will be achieved, if four investigations per day are performed. Retaining all parameters, which do not refer to the costs of the FDG, the average amount for one investigation would vary from DM 2000 (no delivery time) to DM 3300 (4 hours of delivery time). Conclusions: The results are in good agreement to the general laws of economic science, according to which an increase of the “number of units” with the same fixed overheads will result in a relative reduction of the costs of the “products”. A further increase in the frequency of investigations will lead to a rise of the average costs per investigation, because of the physical decay of the FDG delivered once a day.
Keywords: PET; costs; cost-effectiveness; satellite concept; FDG